A Signal Detection Analysis of the Effects of Alcohol on Visual Contrast Sensitivity. (December 2016) - Timney, Brian; Ferreira, Melissa; Matson, Steven
Numerous studies have shown that acute ethanol consumption can reduce visual contrast sensitivity when measured using traditional psychophysical methods. However, no consideration has been given to whether nonsensory factors may also play a role. The present study used both traditional techniques and signal detection procedures to evaluate this possibility. In three within-subject experiments, 41 observers (19 Females and 22 Males) were presented with faint, contrast-modulated, visual patterns and asked to say if they had seen them. In Experiment 1, contrast thresholds were measured using a randomly interleaved staircase procedure, and the data confirmed an increase in threshold following alcohol. In Experiment 2, using similar stimuli, but applying a signal detection analysis, we found that sensitivity, as reflected in d ', did not change following alcohol. However, participants became more conservative in their response criterion. The third experiment was designed to allow thresholds to be measured directly with a conventional psychophysical procedure while permitting a signal detection analysis to be performed on the same data. The conventional psychophysical task showed an increase in contrast threshold, while the signal detection analysis showed no change in sensitivity, but a shift to a more conservative criterion. These data highlight the importance of taking into account alcohol's effects on cognitive processes, even when assessing basic sensory function.